Evaluation of the book and periodical collections of the College of Allied Medical Professions - De Leon, Rosa I. (2003)
The College of Allied Medical Professions, University of the Philippines was the first school in the Philippines to offer the Bachelor of Science degree in Occupational Therapy, Physical Therapy, Speech Pathology, Masters in Clinical Audiology and Masters in Rehabilitation Science. In its 40 years of existence, the College has always maintained a quality of standards in its graduates who are unparalleled in the practice of their future profession. The professions must provide a vast amount of knowledge for each student. This basic theoretical knowledge must be translated into the practical clinical setting in which all students must go through. Through the College's 39 years of servicing the Filipino public, the College Library has been at the forefront in providing the necessary, adequate, well-selected and organized information for its major clientele, which includes students, faculty, researchers and other users. The College Library is an essential source of information for the intellectual advancement in the health sciences.